THE APPLICATION OF PSAK NO. 45 TO FINANCIAL STATEMENTS A CASE STUDY NON-PROFIT ORGANIZATION HIDAYATULLAH PONTIANAK FOUNDATION YEAR PERIOD JANUARY 2018-DECEMBER 2018 - Dewi, Aprilia Puspa; Dewi, Aprilia Puspa (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
The purpose of this research are to apply PSAK No. 45 in financial statements of Hidayatullah PontianakFoundation which is a non-profit entity that enganged in the social field with the aim of prospering people who live around the orphanage and have not adopted PSAK No. 45 in financial statements report and determine the obstacle factors of Hidayatullah Pontianak Foundation in applying PSAK No. 45. This research is a qualitative research that used PSAK No. 45 to implementing financial statements report and questionnaires to determine the obstacle factors of Hidayatullah Pontianak Foundation that use unrequired PSAK No. 45. The results of this research showed that Hidayatullah Pontianak Foundation can?t apply PSAK No. 45 in financial statements report, to know the obstace factors of Hidayatullah Pontianak Foundation in applying PSAK No. 45 because of treasurer do not know about PSAK No. 45 and Hidayatullah Pontianak Foundation have own financial statements report standard that made simply with understood purpose and there is not direct statements from IAI to Hidayatullah Pontianak Foundation about PSAK No. 45.